Advances in irrigation. - Hillel, Daniel (Academic Press, Inc., 1983)
Advances in Irrigation, Volume 2 covers topics on the developments in the science and practice of irrigation. The book presents articles on irrigation scheduling and applied timing criteria; the problem of energy utilization and management in irrigation; and the relationship between irrigation requirements and crop response in terms of crop-water production functions. The text also includes articles on the development and prospects of irrigation in Australia, as well as the application of a plant-environment model to problems in irrigation. The economic analysis of on-farm irrigation using res.